Assessment of Quality of Life of Chronic Kidney Disease Patients Undergoing Haemodialysis in Peshawar - Iqbal Khan, Ali; Abdullah, Khadija Nowaira; Ali Khan, Arif; Zaman, Saira; Khan, Sumera; Behroz, Zohaib; Shah, Syeda Faiza; Ali, Mazhar; Ahmad, Shabeer; Khan, Uzair Abbas (Journal of Postgraduate Medical Institute, 2025)
Objective: To assess the Quality of Life (QOL) of patients undergoing haemodialysis at the Institute of Kidney Diseases (IKD) Peshawar, identify the challenges faced by them in their physical, psychological, environmental and social domains & evaluate the effects of various demographic factors on their Quality of Life. Methods: A cross sectional study was conducted among 229 patients undergoing maintenance haemodialysis (MHD) at Institute of Kidney Diseases (IKD) Peshawar from 10th June to 15th November, 2023. Patients aged 18 years and above of either sex who had undergone maintenance haemodialysis for at least three month were included in this study. Data was collected using a pre-validated World Health Organization (WHOQOL-BREF) questionnaire & was analysed using SPSS Version 22. Results: The mean age of sample was 41+13.41 years. Out of 229 patients undergoing haemodialysis, males were 68.1% whereas females were 32.9%.The social domain had the highest mean QOL score (54.6 +18.8) while psychological domain showed the lowest score (45.6±13.6). Older age was associated with lower QOL scores in physical (p<.001) and psychological (p=.018) domains. Duration of dialysis was positively correlated with higher QOL scores in physical (p=.033) and psychological domains (p=.032).Single subjects also had better QOL scores in physical (p=.021) and psychological (p=.024) domains than married ones. Males had higher QOL scores in physical (p=.013) and social (p=.008) domains than females. Conclusion: Patients with CKD undergoing haemodialysis had low scores in all four domains. Age, duration, gender & marital status affected one or more domains of QOL. Age was found to be the negative predictor of QOL of patients on maintenance haemodialysis.